2022
DOI: 10.31893/avr.2022005
|View full text |Cite
|
Sign up to set email alerts
|

A review on the diagnosis of feline infectious peritonitis

Abstract: Feline infectious peritonitis or simply FIP is viral disease caused by coronavirus in cats of less than three years of age. It is manifested as extreme inflammatory reaction in tissues surrounding abdomen, kidneys and brain. This review article discusses various diagnostic tests and their merits in the diagnosis of FIP suspected cases with the purpose of definitive diagnosis. This review can help to compare different diagnostic parameters and also raise awareness about their advantages and disadvantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…J. Yousuf et al [15] found that changes in indicators during biochemical blood tests in cats with FIP are variable and often non-specific, but there are several key abnormalities that doctors recommend considering before confirming the diagnosis. Thus, the above-mentioned authors indicate hyperglobulinaemia and hyperbilirubinemia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…J. Yousuf et al [15] found that changes in indicators during biochemical blood tests in cats with FIP are variable and often non-specific, but there are several key abnormalities that doctors recommend considering before confirming the diagnosis. Thus, the above-mentioned authors indicate hyperglobulinaemia and hyperbilirubinemia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hyperglobulinemia is observed in 89% of patients, and hypoalbuminemia or low-normal serum albumin level is observed in 64.5% of patients. A low albumin/globulin ratio (A/G) can be used to evaluate the diagnosis of FIP in patients with hyperglobulinemia and hypoalbuminemia [8]. FIP is difficult to diagnose because of non-specific clinical signs, non-pathognomonic hematological and biochemical abnormalities, and low sensitivity and specificity of tests used in the practical routine [9].…”
Section: Introductionmentioning
confidence: 99%